Precise Neurotransmitter-Mediated Communication with Neurons In Vitro and In Vivo Using Organic Electronics - Daniel T. SIMON; Karin C. LARSSON; Magnus BERGGREN; Agneta RICHTER-DAHLFORS (Journal of Biomechanical Science and Engineering, 2010)
Attempts to interface human-made systems with neural systems are commonly based on direct electrical stimulation or exogenous drug delivery. Few techniques have attempted to mimic neurons' own combination of electronic and chemical signaling with endogenous substances. We demonstrate below the organic electronic ion pump (OEIP), a technology which aims to accomplish just that: electronically controlled delivery of ions, neurotransmitters and other bio-substances. Based on electrophoretic migration through an organic electronic system, delivery is diffusive and non-convective, that is, without fluid flow. Various experiments involving OEIP technology are reviewed, culminating in its use, in an encapsulated form, to modulate sensory function in a living animal. As a first step towards an “artificial neuron”, this technology has significant potential for both neural system interfacing and in the treatment of various neurological disorders.